The Political Structure of Multicultural Society Kesetaraan Dalam Masyarakat Multikultural: Studi Terhadap Masyarakat Indonesia Dalam Merawat Kebhinekaan - Azhar, Purjatian (Pusat penelitian dan Pengembangan Masyarakat (P3M) IAIN Kediri, 2020)
This paper tries to explain how the true concept of multicultural society in Indonesia is. As a country, Indonesia has a complex diversity of cultures, ethnicities, customs, languages and religions. The emergence of problems in society is inseparable from the presence of social friction and stratification between fellow nationals. Therefore, it is important for people to understand multicultural concepts. In this paper, the writer tries to analyze the concept of multicultural society in Indonesia through a book initiated by Bhikhu Parekh, namely Rethingking Multiculturalism. In addition, it is also important to instill multiculturalism education for the younger generation in facing today's more complex lives.